Avoiding Sophistry: A Study of Ibn Rushd’s Summary of Aristotle’s Sophistical Refutations - Haidar, Ahmed Milad ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2015)
This study offers an analytical overview of Aristotle’s treatise "Sophistical Refutations" (Sophist), which is part of the logical corpus later compiled by his students under the collective title "Organon", meaning "instrument" or "tool" in Greek—designed to guide the mind toward correct reasoning. The paper examines the position of this work within Aristotle’s broader logical system, especially its role in exposing flaws in reasoning employed by the Sophists. The Sophists were known for employing logical fallacies, manipulating language, and relying on plausible but unproven premises to dominate debates rather than to uncover truth. Aristotle, in response, developed a systematic critique of these fallacies—both formal and informal—revealing how such arguments can appear convincing while being logically unsound. His analysis not only dissects the rhetorical tactics and false dichotomies used in sophistical reasoning but also serves as a caution against deceptive argumentation aimed solely at victory rather than truth. This paper situates Aristotle's work within its historical and philosophical context, underscoring its foundational contribution to logic and critical thinking.